2006
DOI: 10.1136/gut.2005.073205
|View full text |Cite
|
Sign up to set email alerts
|

Vanilloids in pancreatic cancer: potential for chemotherapy and pain management

Abstract: Background: Success of chemotherapy and alleviation of pain are frequently less than optimal in pancreatic cancer patients, leading to increasing interest in new pharmacological substances, such as vanilloids. Our study addressed the question of whether vanilloids influence pancreatic cancer cell growth, and if vanilloids could be used for pain treatment via the vanilloid 1 receptor (VR1) in pancreatic cancer patients. Methods: In vitro, the effect of resiniferatoxin (vanilloid analogue) on apoptosis and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 59 publications
1
108
0
Order By: Relevance
“…Several lines of evidence support the importance of neurogenic inflammation in the etiology of pancreatitis, including increased pancreatic innervation, elevated neurotransmitter content in pancreatic afferents, and reduction in pancreatitis severity by destruction of primary afferent neurons (Nathan et al, 2002;Hartel et al, 2006;Noble et al, 2006;Schwartz et al, 2013).…”
Section: B Transient Receptor Potential Channels Pancreatitis and mentioning
confidence: 99%
“…Several lines of evidence support the importance of neurogenic inflammation in the etiology of pancreatitis, including increased pancreatic innervation, elevated neurotransmitter content in pancreatic afferents, and reduction in pancreatitis severity by destruction of primary afferent neurons (Nathan et al, 2002;Hartel et al, 2006;Noble et al, 2006;Schwartz et al, 2013).…”
Section: B Transient Receptor Potential Channels Pancreatitis and mentioning
confidence: 99%
“…Capsaicin is one of the major pungent ingredients found in red peppers, which are among the most commonly and frequently used spices in the world (14,15). Due to its analgesic activity, topical application of capsaicin has been used in clinical practice for the treatment of neuropathic pain (16,17). Capsaicin has been revealed to inhibit growth and induce apoptosis in various malignant cell lines (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In other reports, the prognostic values of TRPV5 and TRPV6 were also studied (Hartel et al, 2006), and the results remained controversial. In this study, the level of TRPV5 and TRPV6 showed a tendency of being associated with patients' survival.…”
Section: Discussionmentioning
confidence: 99%